The Role of Literature in addressing Climate Change: An Ecocritical Analysis of Omar El Akkad’s American War - Iqbal, Javed; Khan, Nadeem; Abdullah (Pakistan Languages and Humanities Review, 2024)
Ecocritical analysis of Omar El Akkad’s novel "American War" examines how literature can raise awareness of climate change and its consequences. The study demonstrates how the novel’s dystopian future of environmental catastrophe can spark critical environmental debate. Literature’s power to transform society is key to addressing the global threats posed by climate change, which impacts ecosystems, health, and the economy. The qualitative study analyzes the novel’s themes, characters, and story structures, revealing how it vividly depicts a future America devastated by climate change, rising sea levels, and ecological collapse. Dystopian stories like "American War" underscore the urgency of climate change and promote environmental consciousness in schools and society. Interdisciplinary methods combining literary and environmental science can further expand thinking and engage people in combating climate change.